Analisis Pemahaman dan Implementasi Nilai-nilai Multikulturalisme dalam Hadis Sebagai Landasan untuk Membangun Harmoni Sosial di Era Globalisasi - Siti Kholidah Marbun (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
In the era of globalization, where changes and complexities occur within societies, the multicultural values found within the hadiths become increasingly important in fostering social harmony and maintaining religious tolerance among different communities. Therefore, the understanding and implementation of these multicultural values within the hadiths need to be continuously enhanced and disseminated to the entire society. This study aims to analyze the comprehension and implementation of multicultural values within the sayings of the Prophet Muhammad (peace be upon him), serving as a foundation for building social harmony in the era of globalization. The research method employed is a descriptive-analytical approach. Primary data were collected from hadith collections that pertain to multiculturalism, while secondary data were obtained from relevant journals and books on the discussed theme. The results of this study reveal that the analyzed multicultural values encompass three aspects: the equality of all humans, tolerance, and fair treatment within the framework of human rights. Furthermore, efforts are being made to enhance the comprehension and implementation of these multicultural values, including: 1)Religious education and understanding, achieved through integrating multicultural values into ethics and interpersonal interactions curriculum. 2) Interfaith dialogue, facilitated through grassroots initiatives such as the Interfaith Harmony Forum (FKUB). 3) Dissemination of positive information, accomplished through character education and ethical training. 4) Cross-cultural understanding. These endeavors collectively contribute to fostering a harmonious and inclusive society amidst the challenges and complexities brought about by globalization.